How and why is context important in leadership? - OC, Burak (Institutional Knowledge at Singapore Management University, 2023)
Leadership can be defined as a goal-influence process that occurs between a leader and a follower, groups of followers, or institutions that directs effort towards the achievement of a shared objective (Antonakis & Day, 2018, p. 5). From this definition, we can distil four key elements of leadership: a) leaders, b) followers, c) influence and d) goals, motivation and performance. While leaders and followers are the main actors of leadership processes, how they influence each other has implications for group goals. However, most leadership research focuses on leaders, largely treating them as the sole driver of organisation success or failure (Kelley, 1988; Oc & Bashshur, 2013; Uhl-Bien et al., 2014). One upside of this overemphasis on leaders is a rich body of work on how dispositional characteristics and behaviours of leaders influence followers, the process between leaders and followers, and goals, motivations and performance of the group. The downside, of course, is the short shrift given to followers and other elements of leadership. Where does this leave us with context of leadership? Although not part of the definition, context (along with followers) has become a prominent theme in leadership scholarship. This is because research has highlighted inconsistencies in the relationships between certain leader traits (e.g., extraversion) or behaviours (e.g., transformational leadership) and important leadership outcomes (e.g., individual and group performance).